Role of emerging chitosan and zeolite-modified adsorbents in the removal of nitrate and phosphate from an aqueous medium: A comprehensive perspective - Gopal Italiya; Sangeetha Subramanian (Water Science and Technology, 2022)
Due to industrialization and population growth, freshwater supplies are diminishing and becoming impure with high organic pollutant concentrations such as nitrate and phosphate, which shows a high adverse impact on aquatic and human lives. In drinking water sources, particularly groundwater, nitrate is considered as one of the major pollutants which causes methemoglobinemia (in newborn infants), carcinogenic activities and diabetes. Excess concentration of phosphate leads to eutrophication and death of aquatic species due to reduced dissolved oxygen content. Therefore, all countries must implement highly effective technologies for treating wastewater. Chitosan and zeolite are naturally occurring and cost-effective adsorbent materials with a higher surface area that exhibit greater nitrate and phosphate adsorption. Surface modification of chitosan and zeolite increases the adsorption capacity of adsorbents for the removal of both anions selectively. This paper reviews the current development of modified chitosan and zeolite adsorbents for anion adsorption, with an emphasis on modification by zero and multivalent metals and metal oxides, different surfactants, biomass-derived carbon, and natural and synthetic polymers. Multiple adsorption parameters, optimum adsorption condition, adsorption mechanism, regeneration study, research gap and future aspects have been explained for further research work. HIGHLIGHTS Selection of highly efficient adsorbent materials (chitosan and zeolite) for the removal of nitrate and phosphate from an aqueous solution.; Metal and metal oxide-based chitosan and zeolite composites could be the material for the development of the latest adsorption technology for nitrate and phosphate removal.; Further modification suggestions for enhancing the efficacy of adsorption.;